2021
DOI: 10.1108/jeas-05-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, entrepreneurship and financial openness: evidence from Asia

Abstract: PurposeThis study examines whether financial development affects entrepreneurship, and how financial openness moderate this relationship.Design/methodology/approachThe study employs panel data consisting of 781 country-year observations of 48 countries of Asia for the period 2001–2018.FindingsThe study provides empirical support for the eclectic theory of entrepreneurship in Asian countries. The findings of the study indicate that effective allocation of resources and ease of transactions increases the entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…It does not take into consideration the dynamism and endogeneity in the system. Amin et al (2021) conclude that financial development is crucial for entrepreneurial activities in Asia. Still on the Chinese economy, Jiang et al (2019) employ the kernel density estimation method to analyse the role of the inclusive financial index on farmer entrepreneurship among 22 provinces and 4 municipalities.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 88%
“…It does not take into consideration the dynamism and endogeneity in the system. Amin et al (2021) conclude that financial development is crucial for entrepreneurial activities in Asia. Still on the Chinese economy, Jiang et al (2019) employ the kernel density estimation method to analyse the role of the inclusive financial index on farmer entrepreneurship among 22 provinces and 4 municipalities.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 88%
“…Their results showed that financial development does not encourage entrepreneurship, and that there is a threshold above which financial development has a positive effect on entrepreneurship. [78] found in 48 Asian countries that financial development encourages entrepreneurship.…”
Section: Financial Development and Formal Entrepreneurshipmentioning
confidence: 99%